Univariate Weibull Distributions and Their Applications - Višnja Jurić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The aim of the paper is to bring out the short and concise review of the Univariate Weibull distributions along with their properties. The area of applications is emphasized at the end of the sections.
Keywords: C4; C5; 330; univariate Weibull distribution; multivariate Weibull distribution; application areas; p.d.f; c.d.f; maximum likelihood estimation